Stelarc the body is obsolete - Stelarc, 1946-; Doczy, Krisza; Contemporary Arts Media (Australia : Contemporary Arts Media, 2005)
Documents the performance history of artist Stelarc, from his body suspension to the creation of the prosthetic head and the extra ear
Title from title screen
Speaker: Stelarc
CD-ROM system requirements: Windows PC or Mac
DVD; NTSC
Keywords: Stelarc, -- 1946- -- Criticism and interpretation; Technology and the arts; Performance art